1997
DOI: 10.1007/s004390050588
|View full text |Cite
|
Sign up to set email alerts
|

The Arg 192 isoform of paraoxonase with low sarin-hydrolyzing activity is dominant in the Japanese

Abstract: The high-density-lipoprotein-associated enzyme paraoxonase, which has a role in the detoxification of organophosphorus compounds, is known to be polymorphic in humans. The Arg192 isoform of paraoxonase hydrolyzes paraoxon more rapidly than the Gln192 isoform. However, with respect to the hydrolysis of toxic nerve agents, such as diazoxon, soman, and sarin, the Arg192 isoform displays a lower activity than the other isoform. To evaluate the possibility that the genetic polymorphism was involved in the aggravate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 5 publications
2
22
0
Order By: Relevance
“…Chronic exposure to OPC also gives rise to a condition called COPINDChronic Organo Phosphate induced neuro-psychiatric disorder [15][16][17] . Genetic differences also play important role in Chronic OPC poisoning cases 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Chronic exposure to OPC also gives rise to a condition called COPINDChronic Organo Phosphate induced neuro-psychiatric disorder [15][16][17] . Genetic differences also play important role in Chronic OPC poisoning cases 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Statistical power calculations were performed using Epistat (Finnish Institute of Occupational Health). This study sample size had at least 80% power (two-sided test significant, a of 0.05) to detect an OR of at least 2.5, following the calculations used in previous studies [18][19][20]. We used the dominant model for GSTM1 and GSTT1 and the recessive model for ALDH2 and PON1 in the test analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The genotypes of ALDH2 (rs671) were identified by the method of Harada and Zhang [13] as the homozygous genotype of normal ALDH2 (*1/*1), the homozygous genotype of inactive ALDH2 (*2/*2), and the heterozygous genotype of normal and inactive ALDH2 (*1/*2). The genotype of the Gln192Arg (rs662) polymorphism of the PON1 gene was determined essentially as described previously [19].…”
Section: Genotypingmentioning
confidence: 99%
“…Numerous clinical studies have shown that ethnic groups may differ in their responsiveness to drugs, [25][26][27] and it has also been suggested that racial differences in the catalytic activity of cytochrome P450 (CYP) isozyme may be responsible for the differences in drug kinetics. 28 The International Conference on Harmonization guideline (ICHE5) document "Ethnic Factors in the Acceptability of Foreign Data" recommends the measurement of pharmacokinetic/pharmacodynamic parameters to permit the clinical effects obtained in one population to be extrapolated to a different population.…”
Section: Discussionmentioning
confidence: 99%